Analisis Literatur: Kebijakan Publik Terhadap Kemiskinan Pemuda di DIY - Admiwati, Rini (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2024)
Youth poverty poses a substantial challenge to social and economic progress in the Special Region of Yogyakarta (DIY), despite its cultural richness and human capital potential. Barriers such as limited educational access, scarce job opportunities, and inadequate healthcare persist among DIY's youth. Local government and related bodies have implemented various public policies aimed at tackling these issues. This study conducts a comprehensive literature review analyzing these policies, drawing from academic articles, government reports, and policy documents. It focuses on policy identification, effectiveness assessment, impacts, and factors influencing implementation. Successful policies have notably improved educational and employment opportunities for DIY's youth. However, challenges like bureaucratic complexity, inter-agency coordination issues, and funding limitations hinder comprehensive and sustainable implementation. Continuous policy evaluation is essential to ensure effective poverty alleviation and community benefit. Recommendations emphasize enhancing cross-sector collaboration, implementation coordination, and regular policy monitoring and evaluation to promote inclusive development aligned with DIY youth needs.